Implementation of Decision Support in Mutual Fund Investment Selection using MOORA - Soetam Rizky Wicaksono (TIERS Information Technology Journal, 2023)
This research focuses on the application of the Multi-Objective Optimization method based on Ratio Analysis (MOORA) as part of the Decision Support System (DSS) in the selection of mutual fund investments in Indonesia. The purpose of this study is to help novice investors who often find it difficult to choose mutual funds due to lack of knowledge. Considering that the number of investors continues to increase, especially during and after the pandemic, this research becomes relevant and important. The MOORA method was chosen because of its ease and flexibility in handling various criteria compared to other Multiple Criteria Decision Making (MCDM) methods. The five criteria taken as calculation material are return, risk, cost, liquidity, and reputation of the investment manager. The results showed that the MOORA method is effective in providing objective and data-driven investment recommendations. Considering various relevant criteria and weights, MOORA can provide mutual fund ratings that match investors' preferences and risk tolerance. Thus, this research successfully achieved its goal of assisting novice investors in choosing mutual funds. These results suggest that MOORA can be an important part of DSS in the context of mutual fund investing.